Nanogels and dendritic molecules combined to form a smart nanomaterial. (5th January 2022) - Rosso, Anabella P.; Martinelli, Marisa
Graphical abstract: Highlights: Dendritic thermo-responsive polymer-based NGs were prepared by precipitation. Dendronizacion controls the structural and functional properties. The so-called dendritic effect was evidenced. Dendritic arrangements acted synergistically on the structure/property relationship. Abstract: Dendritic thermo-responsive polymer-based NGs were prepared following the precipitation methodology. PVCL-based dendritic NGs are reported with the incorporation of a dendritic building block, and with different percentages of N, N '-methylenebisacrylamide (BIS) as crosslinker agent. The dendritic moiety employed were di- tert -butyl-4-acryloylamine 4-[2-( tert -butoxy- carbonyl)ethyl]heptanodioate (ABA) and its hydrolyzed compound with peripheral carboxylic groups (ABC). In order to analyze the chemical structure, NGs were characterized using infrared microscopy. Hydrodynamic diameter and phase transition temperature were determined by dynamic light scattering. Phase transition temperature was also measured by UV–vis spectroscopy. Measures of electrophoretic mobility completed the characterization of the NGs. The phase transition temperature and Dh values were regulated by the percentage of crosslinker and the identity, quantity, steric effect, and polar character of the dendron. The polar and steric contributions of the dendritic block (ABA or ABC) were evidenced by the Dh, Tf and ζ values. For the P(VCL-co-ABC)-based dNGs, the hydrodynamic diameter was greater than the homopolymeric P(VCL) NGs, and even greater when the percentage of dendron increases, because of the hydrophilic periphery (acid groups). The presence of ABC allowed intramolecular hydrogen bonding due to the presence of the acid groups, and a decrease in the Tcp value by increasing the dendronization percentage was observed. The hydrogen bond intra- and intermolecular formations have a great impact on the conformation and surface properties. The detailed analysis of the property-structure relationship of the different NGs allowed us to prepare dNGs of nanometric size with a Tcp between 39 and 41 °C, which gives them potential applications in the biomedical area considering the average temperature of the human body.